Challenges and consequences of the drop in pediatric vaccination rates in Brazil - Oliveira, Bárbara Mariana Fernandes Salvador de; Pinto, Camila Karielle Sousa Carvalho; Silva, Emilly Lessa; Cruz, Gabriel Lopes; Vieira, Gabryella Trindade; Carreira, Maria Clara Genelhú; Negreiros, Maria Eduarda Mourão; Meurer, Mateus Merlin; Lopes, Vitória Resende; Silva, Vitor Emanoel Barbosa da (Seven Editora, 2024)
In recent decades, childhood vaccination has played a crucial role in preventing severe disease in children globally. Although it does not have access to specific data from the last 25 years, in general, immunization programs coordinated by health organizations, such as the WHO, have contributed to a significant reduction in the incidence of vaccine-preventable diseases, such as measles and polio. Promoting high rates of vaccination coverage remains a priority to ensure child health and combat infectious disease outbreaks. It is recommended to consult local and international sources for detailed data on childhood vaccination in specific periods and regions. DOI:https://doi.org/10.56238/sevened2024.001-012